Kerouac : his life and work - Maher, Paul, 1963- (Taylor Trade Pub., 2007)
This authoritative biography of writer, poet, and beat generation icon Jack Kerouac (1922-1969) recounts in gripping detail the story of his exceptional life and the key relationships that affected Kerouac's development as an artist, including those with his three wives, numerous girlfriends, and beloved mother. Kerouac presents a fresh and more accurate account of the author of On the Road, one that neither ignores nor wallows in his flaws.